(untitled) (Global Journal of Science Frontier Research, 2025)
In this paper we present a unified approach for determining the reflectance and transmittance properties of single-layer and multilayer optical and quantum thin-film structures using a unified set of equations based on the similarity of classical Maxwell and newly formulated relativistic Dirac vector field equations A review of these field equations and the corresponding wave equations is presented Electromagnetic plane-wave and quantum mechanical matter-wave solutions that satisfy these equations and their properties are reviewed Single-layer optical and quantum thin film analyses lead to a unified set of analytical equations that predict their reflectance and transmittance characteristics A unified theory conversion table describes how to convert classical electrodynamic quantities into relativistic quantum mechanical quantities to use a set of unified equations The unified approach was extended to multilayer optical and quantum mechanical thin-film structures Numerical results are presented for single-layer and multilayer optical and quantum thin film architectures MATLAB software was employed for computations and graphics